Addressing Health Disparities in Adults with Developmental Disabilities - Videlefsky, Andrea S. (Ethn Dis, 2019)
Adults with developmental disabilities are a growing population that experiences significant health disparities due to unmet health care and social needs. Few standardized health care guidelines are available or broadly accepted as best practices for this population. The Adult Disability Medical Healthcare (ADMH) is a community-based clinic that provides a unique multidisciplinary team-based approach to addressing the social and health care needs of adults with developmental disabilities within the framework of a Patient Centered Medical Home model. ADMH is developing the necessary research infrastructure and obtaining input from individuals with developmental disabilities, their families, and community stakeholders and is performing foundational analysis to inform the development of guidelines for evidence-based best practices for the care of adults with developmental disabilities. This will set the stage for future research evaluating the impact of these guidelines on health outcomes and the reduction of health disparities in this population. This commentary highlights a process for development of evidence-based guidelines and best practices for care of adults with developmental disabilities.